Implikasi Prinsip Most Favoured Nation terhadap Pengaturan Tarif Impor Di Indonesia - Dony Yusra Pebrianto (Wajah Hukum, 2018)
The existence of trade liberalization are faced with the fact that competition in the trade of countries particularly in this export and import kian feels very rapidly. The existence of instruments of international law contained in the General Agreement on the set fee and Trade (GATT) becomes an important point in the conception of international trade arrangements for States parties who joined GATT in the World Trade Organization (WTO). So the principles inherent in the preparation of the concept of a national law for countries that have ratified GATT. Indonesia one of the countries that have ratified GATT would of course be bound by those principles, one of which is the principle of Most Favoured Nation tariff arrangements that implicates to import in Indonesia. So the protection of local commodities closed chances though limited to keep the continuity of the national production.